76 Many Forms of Bariatric Surgery Can Be Used to Treat Obese Patients. Is Laparoscopic Gastric Plication the Next Gold Standard?. (28th February 2022) - Cameron, F.
Abstract: Aim: Obesity is growing in prevalence in today's world. Conservative treatment methods often fail; however, bariatric procedures have been developed to help patients lose weight. While bariatric surgery takes various forms, these are often highly invasive or have high rates of complication, leading to further development by surgeons of new procedures. One of the more recently developed procedures is laparoscopic gastric plication- a surgery involving imbrication of the greater curvature of the stomach to narrow the gastric lumen. It has been hypothesised that this could be the next gold standard in the management of obesity. This paper seeks to address such hypotheses by comparing laparoscopic gastric plication with the already established laparoscopic gastric sleeve in the treatment of patients and their comorbidities. Method: By analysing meta-analyses, systematic reviews and case studies on both laparoscopic gastric plication and laparoscopic gastric sleeve, it has been possible to compare the safety, efficacy, and cost of the two procedures. Results: The results of the literature review undertaken indicate no significant difference when the efficacy and cost of the two procedures is compared. Laparoscopic gastric sleeve is, however, a safer procedure with fewer postoperative complications than laparoscopic gastric plication. Conclusions: In conclusion, it is unlikely that laparoscopic gastric plication will be the next gold standard in bariatric surgery unless the procedure is standardised, and its safety record is improved.